Sufi journeys to Anatolia during the Seljuk period of Rum (600-704 AH/1200-1307 AD - Hussain, Ahlam; Al Dohuki , Firsat (Humanities Journal of University of Zakho, 2021)
This research deals with the study of the journeys of the great Sufis who came to Anatolia during the reign of the Roman Seljuks from various regions of the Islamic world. On a land of Christian religion and of a Greek character; Its rulers were obliged to turn it into an area with an Islamic culture, as they were followers of the Abbasid Caliphate, so they embraced scholars and men of Sufism by providing what secures their survival. Anatolia became the destination of Sufism from many regions, especially senior Sufis and others, who contributed to enriching the region religiously and intellectually through their writings and ideas and their effective influence on limit the viewpoint of rulers and inhabitants; Until Anatolia became the largest center of mysticism in the Islamic world during the sixth and seventh centuries AH / the second and thirteenth centuries AD.